Validity of time series kinematical data as measured by a markerless motion capture system on a flatland for gait assessment - Tanaka, Ryo; Takimoto, Haruka; Yamasaki, Takahiro; Higashi, Ariaki (Journal of biomechanics, 2018)
As a cost-effective, clinician-friendly gait assessment tool, the Kinect v2 sensor may be effective for assessing lower extremity joint kinematics. This study aims to examine the validity of time series kinematical data as measured by the Kinect v2 on a flatland for gait assessment. In this study, 51 healthy subjects walked on a flatland while kinematic data were extracted concurrently using the Kinect and Vicon systems. The kinematic outcomes comprised the hip and knee joint angles. Parallel translation of Kinect data obtained throughout the gait cycle was performed to minimize the differences between the Kinect and Vicon data. The ensemble curves of the hip and knee joint angles were compared to investigate whether the Kinect sensor can consistently and accurately assess lower extremity joint motion throughout the gait cycle. Relative consistency was assessed using Pearson correlation coefficients. Joint angles measured by the Kinect v2 followed the trend of the trajectories made by the Vicon data in both the hip and knee joints in the sagittal plane. The trajectories of the hip and knee joint angles in the frontal plane differed between the Kinect and Vicon data. We observed moderate to high correlation coefficients of 20%–60% of the gait cycle, and the largest difference between Kinect and Vicon data was 4.2°. Kinect v2 time series kinematical data obtained on the flatland are validated if the appropriate correction procedures are performed. Future studies are warranted to examine the reproducibility and systematic bias of the Kinect v2.